ARTIFICIAL INTELLIGENCE IN ACADEMIA: OPPORTUNITY OR CHALLENGE? - Grigoryan, L.H.; Badalyan, M. V.; Grigoryan, A.Z. (Aktualʹnì problemi rozvitku ekonomìki regìonu (Online), 2025)
In recent years, the rapid advancement of Artificial Intelligence (AI) has had a profound and transformative impact across a wide range of sectors, including education and scientific research. As the primary environment for the generation, exchange, and preservation of knowledge, academia finds itself at the forefront of this technological shift. AI presents a dual reality for academic institutions: it brings forward unprecedented opportunities for innovation and efficiency, while simultaneously introducing complex ethical, pedagogical, and operational challenges. This article aims to examine the multifaceted influence of AI on higher education, particularly focusing on the evolving role of educators. While numerous studies have explored AI's applications in learning management systems, automated grading, and research data analysis, this paper places a particular emphasis on the human dimension namely, how academic staff are responding to the integration of AI tools into their teaching and research practices. Through an analytical overview, the paper identifies both the benefits and risks associated with AI implementation in academia. On the one hand, AI offers the potential to enhance personalized learning, automate repetitive administrative tasks, and improve access to educational resources. These advancements could significantly increase productivity and support more inclusive educational practices. On the other hand, the growing reliance on AI raises serious concerns related to academic integrity, data privacy, algorithmic bias, and the potential deskilling of educators. The article highlights the urgent need for clear institutional strategies that include professional development for educators, ethical guidelines for AI use, and investment in digital infrastructure. Without these measures, the integration of AI could lead to fragmentation and inequality within the academic system. Educators must not only adapt to technological innovations but also actively shape the discourse around the responsible and meaningful use of AI in education. In conclusion, while AI undoubtedly holds transformative potential for academia, its successful and ethical implementation depends on a balanced approach one that values both innovation and the enduring principles of academic freedom, critical thinking, and human-centered learning. Останніми роками стрімкий розвиток штучного інтелекту (ШІ) справив глибокий і трансформаційний вплив на широкий спектр сфер, зокрема на освіту та наукові дослідження. Як головне середовище для створення, обміну та збереження знань, академічна спільнота опинилася на передовій цієї технологічної трансформації. ШІ створює для закладів вищої освіти подвійну реальність: з одного боку, відкриваються безпрецедентні можливості для інновацій та підвищення ефективності, з іншого постають складні етичні, педагогічні та організаційні виклики. Метою цієї статті є аналіз багатовимірного впливу ШІ на вищу освіту, з особливим акцентом на зміну ролі викладача. Хоча чимало досліджень уже розглядали застосування ШІ в системах управління навчанням, автоматизованому оцінюванні та аналізі наукових даних, ця робота приділяє особливу увагу саме людському аспекту тому, як академічні працівники реагують на впровадження ШІ у викладацьку та наукову діяльність. Через аналітичний огляд у статті висвітлюються як переваги, так і ризики, пов’язані із застосуванням ШІ в академічному середовищі. З одного боку, ШІ може сприяти персоналізації навчання, автоматизації рутинних адміністративних завдань і покращенню доступу до освітніх ресурсів. Такі досягнення можуть суттєво підвищити продуктивність і підтримати інклюзивні освітні практики. З іншого боку, зростаюча залежність від ШІ викликає серйозне занепокоєння щодо академічної доброчесності, захисту даних, алгоритмічної упередженості та потенційної втрати кваліфікації викладачів. У статті підкреслюється нагальна потреба у чітких інституційних стратегіях, які включають професійний розвиток викладачів, етичні керівні принципи щодо використання ШІ та інвестиції в цифрову інфраструктуру. Без таких заходів інтеграція ШІ може призвести до фрагментації та нерівності в системі вищої освіти. Викладачі мають не лише адаптуватися до технологічних змін, а й активно формувати дискурс навколо відповідального й осмисленого використання ШІ в освіті. У підсумку, хоча ШІ, без сумніву, має трансформаційний потенціал для академічної сфери, його успішне й етичне впровадження залежить від збалансованого підходу — такого, що поєднує інновації з непорушними принципами академічної свободи, критичного мислення та орієнтованого на людину навчання.